Piezoceramic-polymer and piezoceramic-cement composites: A brief review - Suchittra Inthong (2019)
© 2019 Chulalognkorn University. The physical properties of piezoceramic-polymers and lead-based or lead-free - Portland cement or geopolymer are described as part of this brief review. The connectivities such as 0-3, 1-3, 2-2 and 3-3 were employed to fabricate the composites. Their physical properties such as dielectric, coupling constant, acoustic impedance etc. were measured. The acoustic impedance obtained from the PZT-epoxy resin (0-3/1-3 connectivity) showed quite low. This can be further developed to match with water or human tissue for both hydrophone and medical applications. The properties of the composites containing lead-based or lead-free cement or geopolymer were also revealed. The results prove that these composites have a high potential to be employed as green building materials and smart concrete sensors in the future. A thin film of piezopolymer-metal oxide composite could also be developed to perform energy harvesting properties.